Bullous skin lesions in a jaundiced infant after phototherapy: a case of congenital erythropoietic porphyria - Baran, Maşallah; Eliaçık, Kayı; Kurt, İsmail; Kanık, Ali; Zengin, Neslihan; Bakiler, Ali Rahmi (The Turkish Journal of Pediatrics, 2013)
Congenital erythropoietic porphyria is a rare autosomal recessive disorder of porphyrin metabolism in which the genetic defect is the deficiency of uroporphyrinogen III cosynthase (UIIIC). Deficiency of this enzyme results in an accumulation of high amounts of uroporphyrin I in all tissues, leading to hemolytic anemia, splenomegaly, erythrodontia, bone fragility, exquisite photosensitivity, and mutilating skin lesions. We discuss a female infantile case who was admitted for jaundice; bullous lesions appeared on her trunk during phototherapy in the neonatal period. The skin biopsy findings were consistent with epidermolysis bullosa. Due to persistent hepatosplenomegaly and cholestasis, metabolic tests and liver biopsy were performed. During the follow-up, hemolytic anemia and red urine were detected. The levels of porphyrin metabolites were determined at high concentrations in plasma, stool and urine analysis, which were suggestive of congenital erythropoietic porphyria.